Analisis Materi Ajar Pendidikan Agama Islam dan Budi Pekerti SMP Kelas VIII Perspektif Hots - Dewi Afiatul Qutsiyah; Hasyim Asy’ari (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The 2013 curriculum is structured to improve 21st century skills requiring teachers to play an important role in training students to develop higher-order thinking skills. Therefore, the approach used is the High order Thinking Skills (HOTS). The purpose of this study is to analyze Islamic religious education teaching materials and manners for class VIII HOTS perspective. This research is a content analysis research with a qualitative approach. The data obtained from this study were sourced from the revised 2017 edition of the Islamic Religious Education and Moral Education Textbook for class VIII SMP/MTs. Meanwhile, the data taken by the researcher was an explanation of the material in it related to themes 1 to 3. The research techniques used namely the documentation technique. Analysis of the data used is the content analysis of the Philip Mayring model. The results showed that in substance chapters 1-3 there are still materials that are categorized as HOTS, for example Creating (37.5%), Analyzing (28%), and there are no activities that are included in the evaluation criteria, but there are some activities that are categorized as LOTS, For example Remembering (18.7%), Understanding (15.6%), and there are no activities that include the criteria for applying.